Maybe the second one or third one
So, u would start by expanding the bracket and ignoring the 2 at the moment.
(x+9)(x+9)= x^2-18x+81(using the foil method!
Then u would put 2 at the front to get:
2(x^2+18x+81)
= 2x^2+36x+162
<span>x=<span>−<span><span>2<span> and </span></span>y</span></span></span>=<span>−<span>2
</span></span>A.(−2, −2)
Answer:
D
Step-by-step explanation:
gradient for the line y=5x+2 = 5 from y=mx+c where m =gradient
parallel lines have equal gradients thus M2=5
equation for line passing through point (-6,-1) and gradient , m=5 will be
(change in y/change in x)=M2
(y--1/x--6)=5
y+1/x+6 =5
y+1=5(x+6)
y+1=5x+30
y=5x+29